JUST TECHNOPANIC OR A REAL RISK? PUBLISHING CHILDREN’S PICTURES ONLINE: A REVIEW OF LITERATURE - Tuikong, Sylvia (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
The internet has become an essential resource for social interaction among children, but it brings with it both advantages and disadvantages that depend in part on how it is used. This study, which is anchored in social learning theory, employed a desktop review of existing literature that focused on Kenya but covered global and other regional levels as well. The study found a number of benefits of the internet for children: updating family and friends on new developments in the children’s lives, reviewing photos and other records of past events, engaging in online interactions, and increasing their capacity for learning. Nonetheless, there are also internet-specific risks, such as access to inappropriate content and unsafe interactions with other children or adults. Other risks include “digital kidnapping” and contact with perpetrators who encourage children to engage in sexual activity. Although some countries have policies on internet usage, few have specific policies or guidelines addressing children’s vulnerability when sharing their pictures online. Moreover, most such policies are not applied in practice, especially in African countries. The study recommends developing and implementing policy frameworks to protect children online and using privacy settings to protect their information.